Causas y efectos del cobro de las pensiones alimenticias a través del apremio personal del alimentante, de conformidad al art.147 del código de la niñez y adolescencia - Salazar Cárdenas, Paola Fernanda (2015)
This work aims to design an appropriate legal regulations regarding the obligor prison for non-payment on alimony, especially proposing reform that would prevent this kind of arbitrariness. This research dedicates part of his development to address what constitutes and concerns the administration of justice, especially the constitutional reforms governing personal urgency of the obligor, aspects, with realistic and positive to bring out the good sense and also what wrong and poor of our legal framework in Ecuador with accurate, sufficiently broad and democratic arguments. As the legal rules to regulate this common problem in our society it was designed. This proposed reform is the foundation due before topics are discussed raise it consistent with this problems such as: The right of children in Ecuador , in which a brief history and a chronological analysis of the Rights of Children is performed in the current framework; is also the Constitution of the Republic in which its trajectory is analyzed, its fundamental and general principles and rights of freedom ; in the Code on Children and Adolescents , in which an analysis is made of the same; addition to the legal basis for constitutional reforms over a field investigation to be aware of and to observe qualitatively the extent of this problem.